Creatine supplementation improves phosphagen energy pathway during supramaximal effort, but does not improve anaerobic capacity or performance - De Araujo Bonetti De Poli, Rodrigo [UNESP]; Roncada, Luan Henrique [UNESP]; De Souza Malta, Elvis [UNESP]; Artioli, Guilherme Giannini; Bertuzzi, Rômulo; Zagatto, Alessandro Moura [UNESP] (Frontiers, 2019)
This study aimed to investigate the effects of short-duration creatine monohydrate supplementation on anaerobic capacity (AC), anaerobic energy pathways, and time-to-exhaustion during high-intensity running. Fourteen healthy men underwent a graded exercise test (GXT) followed by a VO2max confirmation test, 5 submaximal efforts, and 4 supramaximal running bouts at 115% of VO2max intensity (the first two supramaximal sessions were applied as familiarization trials) to measure the AC using two procedures; the maximum accumulated oxygen deficit (MAOD) and non-oxidative pathways energetics sum (AC[La-]+EPOCfast). The investigation was conducted in a single-blind and placebo-controlled manner, with participants performing the efforts first after being supplemented with a placebo (dextrose 20 g·day-1 for 5 days), and then, after a 7 day placebo washout period, they started the same procedure under creatine supplementation (20 g·day-1 for 5 days. This order was chosen due to the prolonged washout of creatine. MAOD was not different between placebo (3.35 ± 0.65 L) and creatine conditions (3.39 ± 0.79 L; P = 0.58) and presented a negligible effect [effect size (ES) = 0.08], similar to, AC[La-]+EPOCfast (placebo condition (3.66 ± 0.79 Land under creatine ingestion 3.82 ± 0.85 L; P = 0.07) presenting a small effect (ES = 0.20). The energetics from the phosphagen pathway increased significantly after creatine supplementation (1.66 ± 0.40 L) compared to the placebo condition (1.55 ± 0.42 L; P = 0.03). However, the glycolytic and oxidative pathways were not different between conditions. Furthermore, time to exhaustion did not differ between placebo (160.79 ± 37.76 s) and creatine conditions (163.64 ± 38.72; P = 0.49). Therefore, we can conclude that creatine supplementation improves the phosphagen energy contribution, but with no statistical effect on AC or time to exhaustion in supramaximal running.
Keywords: Anaerobic capacity; Creatine; Energy contribution; High-intensity effort; Performance